2021
DOI: 10.3389/fonc.2021.764065
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of T Stage and the Number of Pathologic Lymph Nodes Provides Better Prognostic Discrimination in Early-Stage Cervical Cancer With Lymph Node Involvement

Abstract: ObjectiveStage I and II cervical cancer with pelvic and/or para-aortic lymph node (LN) metastases are upstaged to stage IIIC under the new FIGO 2018 staging system, and radical chemoradiotherapy was recommended. But heterogeneity in outcome existed in this group of patients. We conducted this retrospective analysis to evaluate the heterogeneity of these patients and tried to provide a more detailed classification to reflect the prognosis and guide the treatment. We also evaluated the efficacy and toxicity of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Information about para‐aortic LN metastasis was not available in the study; hence, there was only a single IIIC1 cohort. Bai et al 21 performed a survival analysis of 242 patients with early cervical cancer and LN‐positive disease to determine its prognostic factors. That study reported that T stage was an independent prognostic factor for DFS and OS and that patients with Stage T2 disease had a poorer prognosis than those with Stage T1 disease (T1 vs. T2, 5‐year OS: 86% vs. 58%, p = 0.001; 5‐year DFS: 80% vs. 20%, p = 0.007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Information about para‐aortic LN metastasis was not available in the study; hence, there was only a single IIIC1 cohort. Bai et al 21 performed a survival analysis of 242 patients with early cervical cancer and LN‐positive disease to determine its prognostic factors. That study reported that T stage was an independent prognostic factor for DFS and OS and that patients with Stage T2 disease had a poorer prognosis than those with Stage T1 disease (T1 vs. T2, 5‐year OS: 86% vs. 58%, p = 0.001; 5‐year DFS: 80% vs. 20%, p = 0.007).…”
Section: Discussionmentioning
confidence: 99%
“…We particularly excluded cases with preoperative treatment or underdosage of radiotherapy according to the NCCN guidelines. Laparoscopy cases were also excluded to rule out deviation, because Bai et al 21 reported that in women with early cervical cancer, the DFS and OS rates after minimally invasive radical hysterectomy were lower than those after open radical hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 Since the introduction of 2018 FIGO staging system, there have been increasing concerns regarding the reliability of 2018 FIGO stage IIIC due to considerable heterogeneity in classifying lymph node metastases, regardless of tumor size or number of nodal metastases. [14][15][16][17][18][19] For example, a study from National Cancer Database (NCDB) reported that the 5-year survival rates of FIGO 2018 stages IA, IB, II, and III were 94%, 86.3%, 66.9%, and 47.7%, respectively. The 5-year survival rate of stage IIIC1 was 61.9%, while the 5-year survival rates of IIIC1 with T1a, T1b, T2 and T3 stages were 95.8%, 80.3%, 57.2%, and 39.7%, respectively.…”
Section: Introductionmentioning
confidence: 99%